495 Virtual Reality Simulation Training in Hip Surgery Versus Traditional Surgical Education Method: A Systematic Review of Randomised Controlled Trials. (19th August 2022) - Tsinaslanidis, P; Choudhury, A; Smith, T; Hing, C
Abstract: Aim: The purpose of this study was to perform a systematic review of the effects of orthopaedic virtual reality simulators on surgical skills across randomised controlled trials. Method: The authors searched PubMed, CINAHL, MEDLINE, AMED, Eric, Embase, Cochrane Central Register of Controlled Trials, TRIP database and grey literature from 1946 to November 2020. Inclusion criteria were all level one studies, specifically randomised controlled trials with orthopaedic training simulators in hip surgery and clear evaluation of skills attained after virtual reality simulation (VR) training. The primary outcome was the reported quantitative assessment of operative skills acquisition. The Jadad scale was used as a tool in order to appraise the methodological quality of the included trials. The data collected were not amenable for meta-analysis as they were too heterogenous and were analysed and presented using a narrative analysis and the Synthesis Without Meta-analysis (SWiM) reporting guideline. Results: A total of 1095 articles were identified. Four level I studies, all randomised controlled trials, including 86 participants were eligible for the final analysis. There were significant differences in the types of simulators, training structure, validity types, performance scores and outcome measures described in each study. In three out of four studies (75%) the use of VR training simulators led to improved surgical skills acquisition compared to other traditional teaching methods. Conclusions: Overall, this review showed that the use of VR simulation training is a potential tool that can enhance surgical skills acquisition in hip surgery procedures compared to traditional education methods.